Wybrane problemy konstytucyjnej zasady niezawisłości sędziowskiej - Kania, Agnieszka (Wydawnictwo Naukowe UAM, 2015)
The purpose of this study is to present a selection of issues relating to the principle of judicial independence. Not aspiring to be a comprehensive discussion of the topic, this article focuses on selected aspects of the principle. On the basis of these aspects, it was sought to prove that the proper application of this principle requires much more than its mere declaration in the normative rules of even the highest rank. Furthermore, the result of the analysis carried out is the conclusion that the legal nature of the principle of judicial independence should not be assessed on the basis of selective provisions of the basic law. In this regard, the regulations of ordinary laws, as well as the developed code of judicial conduct, play an important role. The analysis carried out shows that its character should not be assessed on the basis of selective and random provisions of the basic law. A thorough analysis of the entirety of constitutional and extra-constitutional regulations entitles us, in turn, to argue for the compromise (mixed) presentation of the principle, which would allow us to see in it a conjunction of rights granted and duties imposed on a judge. At the same time it should be noted that what proves signiﬁ cant for the proper working of the principle of judicial independence are not only real guarantees of its existence, but also that they be respected consistently in the government system of the democratic rule of law. It is also pointed out that sometimes the ethical and moral requirements on judges impose on them exaggerated personality traits that would de facto be diffi cult to state and assess, as so far no objective quantiﬁ ers have been worked out which would then be a basis that would enable, setting out clearly or with a high degree of probability that the judge is: (i) impartial, (ii) has a sensitive conscience, (iii) stands out for his or her honesty, (iv) can separate justice from injustice, (v) is responsible for his or her spoken and written words and, is, at the same time, (vi) aware of his or her own independence.
Selected problems of the constitutional principle of judicial independence
Keywords: judicial independence; division of authorities; jurisdiction; the judiciary